Chief Executive Officer Attributes and the Value of the Firm: Does Firm Size Play a Moderating Role? - IMASUEN, Osasere Festus; OKORO, Edesiri Godsday; YAHAYA, Garba Hassan (International Journal of Management and Sustainability, 2022)
This study seeks to (1) assess the relationship between CEO attributes and firm value, and (2) ascertain the moderating role of firm size in the relationship between CEO attributes and firm value, using a panel research design. This study identifies CEO tenure, CEO turnover, and CEO ownership as CEO attributes, Tobin’s Q as a measure of firm value, and the natural logarithm of total assets as a measure of firm size. Data were sourced from the database of Machameratios for the period 2010 to 2019 and analyzed using fixed and random effects regression and structural equation modeling. First, the fixed and random effect result revealed that CEO tenure, turnover, and ownership negatively affect the value of the firm; however, the relationship was only significant for CEO tenure and ownership. Second, the structural equation modeling result showed that while firm size does not play a significant moderating role in the relationship between CEO tenure and turnover and firm value, a significant moderating (negative) effect was found for CEO ownership. The study recommends that since CEO turnover and tenure do not matter to the value of the firm, there is a need to ensure that a CEO’s term in office is not lengthened beyond what is required by tenure legislation, i.e., it should not exceed 4 years. In addition, for larger firms, CEO shareholding should be adequately managed to positively affect the value of the firm.